Automated Gain Measurement System for Wide-Band Antenna Based on Instruments Remote Access Techniques: Direct SCPI Commands - Ali Ameen Mohammad; Bashar Alwannos; Alaa Salman (Pakistan Journal of Engineering & Technology)
A novel approach to wide-band antenna gain measurement is presented in this article, offering practical solutions to address the challenges posed by traditional measurement methods. The proposed system enhances efficiency, reduces complexity, and improves accuracy, making it a valuable tool for antenna testing in research and industry settings. A discussion of the challenges and complexities involved in measuring the specifications of manufactured antennas is made. We are particularly focusing on wide-band antenna gain measurement. It highlights the need for special equipment and expertise to conduct these tests effectively, especially for wide-band antennas. The proposed automated measurement system aims to simplify and streamline the gain measurement process by remotely driving the necessary instruments and reducing the complexity of the measurement mechanism. The novelty of this new automated measurement system can be divided into two branches. The first branch improves the standard approach of wide-band antenna gain measurement. The second branch modifies the structure of the software of the traditional remote access applications by mixing the operational instructions of the instrument with the direct SCPI commands. The resulting software has the ability to remotely drive many instruments synchronically, reducing the number of experienced people needed to complete the measurement process.